Effects of Extended Postmortem Interval on Microbial Communities in Organs of the Human Cadaver - Lutz, Holly; Vangelatos, Alexandria; Gottel, Neil; Osculati, Antonio; Visona, Silvia; Finley, Sheree J.; Gilbert, Jack A.; Javan, Gulnaz T. (Frontiers in Microbiology, 2020)
Human thanatomicrobiota studies have shown that microorganisms inhabit and proliferate externally and internally throughout the body and are the primary mediators of putrefaction after death. Yet little is known about the source and diversity of the thanatomicrobiome or the underlying factors leading to delayed decomposition exhibited by reproductive organs. The use of bacterial 16S rRNA gene sequences for taxonomic classification and phylogenetic analyses of human postmortem microbiota has recently emerged as a possible tool in forensic microbiology. The goal of this study was to probe the V4 hypervariable region of the 16S rRNA from internal organ tissue to investigate the extent to which microbial associations among different body sites in human cadavers can be used to predict forensically important determinations such as the cause and time of death. We assessed microbiota of organ tissues including brain, heart, liver, spleen, prostate, and uterus collected at autopsy from criminal casework of 40 Italian cadavers with times of death ranging from 24-432 hours. Both the uterus and prostate had a significantly higher alpha diversity compared to other anatomical sites, and exhibited a significantly different microbial community composition from non-reproductive organs, which we found to be dominated by the bacterial orders MLE1-12, Sapropsirales, and Burkholderiales. In contrast, reproductive organs were dominated by Clostridiales, Lactobacillaes, and showed a marked decrease in relative abundance of MLE1-12. These results provide insight into the observation that the uterus and prostate are the last internal organs to decay during human decomposition. We conclude that distinct community profiles of reproductive versus non-reproductive organs may help guide the application of forensic microbiology tools to investigations of human cadavers.